1970
DOI: 10.1002/qua.560040404
|View full text |Cite
|
Sign up to set email alerts
|

The generalized separated electron pair model. 1. An application to NH3

Abstract: AbstractsThe utility of the separated electron pair (SEP) model (strongly orthogonal geminals) is examined quantitatively, for pyramidal and planar nuclear configurations of the NH, molecule. The best SEP wave function computed for each species is capable of recovering about half of the correlation energy obtained by a fairly accurate configuration interaction (GI) calculation, (corresponding to roughly 2 5 O b of the total molecular correlation energy). I t is illustrated that the model can be systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The transformation matrices of AO basis to CMO and CMO basis to LMO, respectively, are in good agreement with earlier investigations [12,13,14,15]. The calculated coefficients for the AO ~ CMO and CMO ~ LMO matrices on the example of H20 moleeule are given in Table I.…”
Section: Construction Of Localized Orbitalssupporting
confidence: 89%
“…The transformation matrices of AO basis to CMO and CMO basis to LMO, respectively, are in good agreement with earlier investigations [12,13,14,15]. The calculated coefficients for the AO ~ CMO and CMO ~ LMO matrices on the example of H20 moleeule are given in Table I.…”
Section: Construction Of Localized Orbitalssupporting
confidence: 89%
“…[2][3][4][5][6][7] Sometimes this model is referred to as separated electron pair ͑SEP͒ theory. [8][9][10][11][12] Most prior studies focused on the total amount of correlation energy recovered by the product of strongly orthogonal geminals. It was generally concluded that the model has its limitations, primarily attributable to either lack of intergeminal correlation, 5 strong orthogonality approximation, 13 or both.…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing proton number on the same central atom the correlation energy is expected to increase slightly. 16 The neglect of relativistic effects is known to cause errors mostly in the core ionization energies. The relativisitic correction, of course, is greater for the neutral species than that for the positive ion, and increases fast with the atomic number.17…”
Section: O2 -mentioning
confidence: 99%